LO061: Variation in emergency department use of computed tomography for investigation of acute aortic dissection. (2nd June 2016) - Ohle, R.; Luo, L.; Anjum, O.; Bleeker, H.; Perry, J.J.
Abstract : Introduction: Acute aortic dissection (AAD) is a life threatening condition making early diagnosis critical. Although 90% present with acute pain, the myriad of associated symptoms can make investigation and diagnosis a challenge. Our objectives were to assess emergency physician use of CT, yield of CT and ordering variation among physicians in patients presenting with pain for diagnosis of AAD.Methods: This historical cohort study of consecutive adult patients presenting to two tertiary academic care EDs over one calendar year included patients with a primary complaint of non-traumatic chest, back, abdominal or flank pain. Patients were excluded if clear diagnosis was made by basic investigations or exam. Primary outcome was rate of CT Thorax or Thorax/Abdomen ordered to rule out AAD as per clinical indication on diagnostic requisition. Secondary outcome was variation in CT ordering. Variation was measured with; Cochrane q test for homogeneity, proportion of positive CT's (z-test) and mean CT's (t test) ordered between high (>5CT/yr) and low (<5CT/yr) test users. Sample size of 6 per group was calculated based on an expected delta in mean CT ordered of 5 and a within group SD of 3.Results: 31, 201 patients presented with chest, abdominal, back, flank pain during the study period. 8, 472 were excluded based on a diagnosis made by clinical exam or basic investigations. 22, 776 were included (Mean 47years SD 18.5yrs 56.2% Female). Most common diagnoses; Chest pain NYD(23.3%), Abdominal pain NYD(20.8%), Lower back pain NYD(10.5%), Renal Colic (5.3%), ACS (2.9%). CT was ordered to rule out AAD in 175 (0.7%) (Mean 62 years SD 16.5, 50.6% Female). Only 4(2.3%) were found to have an AAD. There was significant variation (range 0.6-12% Q test P<0.027) between proportion of CT's ordered by physicians. Between high (Mean 7.9 n=10 AAD=2) and low test users (Mean 2.3 n=41 AAD=2), there was significant difference in mean number of CT's ordered (p<0.001) but no difference in number of AAD found (p<0.2). No AAD were missed.Conclusion: Current rate of imaging for aortic dissection is appropriately low but inefficient, with 98% of advanced imaging negative. There is significant variation in physician CT ordering (almost 20-fold) without an increase in diagnosis. These findings suggest great potential for more standardized and efficient use of CT for the diagnosis of AAD.